Unorthodox Expenditure Procedures in CEMAC and WAEMU Countries - Imbert, Bruno (IMF Working Papers; Working Paper, 2022)
This paper takes stock of unorthodox expenditure procedures in CEMAC and WAEMU countries and assesses their potential fiscal impact. "Unorthodox procedures" are defined as spending practices that bypass legal provisions governing public expenditure processes and circumvent regular controls or other budgetary rules, including those related to budget time limits, approved ceilings, or approved appropriations. The paper shows that despite PFM reforms, recourse to such procedures has persisted-resulting in the accumulation of arrears; inadequate fiscal reporting, including large stock-flow adjustments; and corruption vulnerabilities.